PENGARUH KONSUMSI KOMBINASI JUS BAYAM MERAH DAN MADU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI KLINIK BIDAN SUMIARIANI TAHUN 2025 - Hayati, Erlina .; Sari, Husna; Nasution, Naimah (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Abstract Anemia in pregnant women is a common health problem that can negatively impact the mother and fetal development. Based on the 2023 Indonesian Health Survey (SKI), it was recorded that 27.7% of pregnant women in Indonesia suffer from anemia. This study aims to determine the effect of consuming red spinach juice mixed with honey on increasing hemoglobin (Hb) levels in anemic pregnant women at the Sumiariani Clinic. Primary data were collected through observation sheets before and after the intervention. Using a purposive sampling technique, 16 respondents were selected because they were identified as having anemia. This study used a pretest and posttest design without a comparison group. For one week, respondents were asked to consume a mixture of red spinach juice and honey twice daily, morning and evening. Hb levels were measured using a digital GCHb device. The results showed a statistically significant increase in hemoglobin levels, from an average of 9.63 g/dL to 11.19 g/dL after the intervention, with a p-value <0.05. This indicates that the null hypothesis is rejected and consumption of the combination has a significant effect on increasing Hb. Thus, red spinach juice and honey can be a safe natural alternative treatment for anemia in pregnant women, as long as it is combined with the consumption of nutritious foods rich in iron.